2017
DOI: 10.1111/aji.12788
|View full text |Cite
|
Sign up to set email alerts
|

Placental exosomes: A proxy to understand pregnancy complications

Abstract: Exosomes (30- to 150-nm particles), originating from multivesicular bodies by the invagination of the endosomal membrane, are communication channels between cells. Exosomes are released by various cell types and cargo proteins, lipids, and nucleic acids reflecting the physiologic status of their cells of origin and cause functional changes in recipient cells, which are likely dependent on their quantity and/or cargo contents. Recently, placental exosomes, produced by various placental cell types, have been iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 113 publications
(112 reference statements)
3
94
0
Order By: Relevance
“…To analyze EVs specifically from syncytiotrophoblasts (STB) of the explants, magnetic nanoparticles (MNPs) coupled to anti‐PLAP antibody, an antigen specific to STB, were used. EVs were labeled with BODIPY‐FL as described in Methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze EVs specifically from syncytiotrophoblasts (STB) of the explants, magnetic nanoparticles (MNPs) coupled to anti‐PLAP antibody, an antigen specific to STB, were used. EVs were labeled with BODIPY‐FL as described in Methods.…”
Section: Resultsmentioning
confidence: 99%
“…We found that STB‐specific EVs can be captured from placental villous culture supernatants using anti‐PLAP‐MNPs. PLAP is a sialoglycoprotein enzyme present almost exclusively on STBs and has been used as a marker of STB‐derived EVs . We first demonstrated specificity of capture by demonstrating that anti‐PLAP‐MNPs capture significant amounts of EVs from placental villous explants but very few EVs from culture supernatants of amnion explants.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Our study has identified novel exomiR in pregnancy which is linked to cancer biological processes such as immune evasion, migration and proliferation. (2) We propose that these specific targets can be used to engineer exosomes which target cancer cells to correct biological processes in preventing metastasis. (3) Preclinical trials which will involve testing in multiple in vivo models to assess efficacy in delivery and tumour cell reprogramming.…”
Section: Future Experimental Framework For the Repurposing Of Exosomamentioning
confidence: 99%
“…Recent interest in the bioactive properties of exosomes in the pathophysiology of complex diseases such as cancer [1], pregnancy complications [2] and HIV [3] has been at the forefront of research and development. Exosomes are classified as nanovesicles ranging from a size of 50 to 120 nm and are released from the cell via the lysosomal pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation